Tradisi Tuturan Na’u Nena Ata Nika Etnik Roworeke Kabupaten Ende Flores: Kajian Linguistik Kebudayaan - Veronika Genua; Dominika Dhapa; Nilda Fatmala (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2021)
The purpose of this paper is to describe the nau nena or nika utterances of the Roworeke Ende Flores ethnic tradition which is still inherited today. The nau nena ata nika speech is a speech in the form of a message or blessing for a young couple who will form a new household. The formulation of the problem raised is, what is the form, meaning, and function of the speech of nanu nena or nika adat in the Roworeke ethnicity. The aim is to find and describe the form, meaning, and function of nau nena or nika speech. The theory used in this study is the theory of cultural linguistics which examines the covariative relationship between language and culture. The method used is descriptive qualitative to describe the form, meaning, and function of nau nena or nika speech. The results obtained are examining the micro and macro linguistic levels. Micro linguistics includes phonological forms related to sound play and sound equations. Morphological studies include, verbs, promomina, numeralia, adjectives, adverbs and also language style. There are also meanings contained in it, namely, the meaning of prohibition, command, hope, togetherness and advice. Next there are aesthetic functions, informative functions and regulatory functions.